Distribution of Pneumonia for Toddlers in North Sumatra Province: Analysis of Health Profile Data in 2019 - Salsabilah, Salsabilah; Putri, Siti Fatma Ayunda; Sumarni (Journal of Epidemiology and Health Science, 2026)
Background: Pneumonia remains the leading cause of mortality among children under five worldwide. According to the Banda Aceh Health Office Report (2018), the number of under-five children affected by pneumonia has increased annually. The highest number of pediatric pneumonia cases was reported in the working area of the UPTD Banda Raya Primary Health Center. This study aimed to identify risk factors associated with pneumonia among children under five in the working area of UPTD Banda Raya Primary Health Center, Banda Aceh, in 2019. Objective: This study also aims to describe the distribution of pneumonia cases in North Sumatra Province during the 2019 period based on secondary data obtained from the Provincial Health Profile. Methods: This study employed a case-control (retrospective) design. The study population consisted of all children aged 12–59 months, with a total sample of 142 participants. Data were analyzed using univariate and bivariate approaches. Bivariate analysis was conducted using the Chi-square test with a 95% confidence level (p-value < 0.05). Results: The results indicated that the significant risk factor associated with pneumonia incidence was house ventilation area (OR = 15.81; 95% CI = 4.70–53.12; p = 0.0001). In contrast, child age (OR = 1.15; 95% CI = 0.54–2.43; p = 0.705), sex (OR = 1.11; 95% CI = 0.57–2.16; p = 0.737), maternal knowledge (OR = 0.38; 95% CI = 0.12–1.24; p = 0.112), and housing density (OR = 1.80; 95% CI = 0.78–4.13; p = 0.163) were not significantly associated with pneumonia incidence among children under five in the study area. Conclusion: The primary risk factor associated with pneumonia among children under five is inadequate house ventilation. Therefore, improving environmental sanitation and promoting clean and healthy living behaviors are essential preventive measures to reduce the incidence of pneumonia. Keywords: under-five pneumonia, health distribution, North Sumatra, health profile